2000
DOI: 10.1242/jcs.113.10.1677
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion and motility depend on nanoscale RGD clustering

Abstract: Integrin adhesion receptors play a crucial role in regulating interactions between cells and extracellular matrix (ECM). Integrin activation initiates multiple intracellular signaling pathways and results in regulation of cell functions such as motility, proliferation and differentiation. Two key observations regarding the biophysical nature of integrin-mediated cell-matrix interactions motivated the present study: (1) cell motility can be regulated by modulating the magnitude of cell-substratum adhesion, by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
278
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 857 publications
(300 citation statements)
references
References 48 publications
21
278
1
Order By: Relevance
“…Traditionally, cell adhesion and proliferation are considered to be inhibited on the soft matrix. However, the matrix stress relaxation successfully compensates for the effect of reduced stiffness on cell adhesion by enabling ligand accumulation after matrix softening [ 44 , 45 ]. This process activates integrin adhesion, actin assembly, and myosin contractility and thereby promotes cell mechanotransduction.…”
Section: Deformable Materialsmentioning
confidence: 99%
“…Traditionally, cell adhesion and proliferation are considered to be inhibited on the soft matrix. However, the matrix stress relaxation successfully compensates for the effect of reduced stiffness on cell adhesion by enabling ligand accumulation after matrix softening [ 44 , 45 ]. This process activates integrin adhesion, actin assembly, and myosin contractility and thereby promotes cell mechanotransduction.…”
Section: Deformable Materialsmentioning
confidence: 99%
“…The concentrations of proteins adsorbed to the surface can be readily controlled and gradients in the density of surface-bound proteins can be formed. Both parameters are known to influence on cell spreading and migration [18][19][20][21][22] . Since an additional gradient can be set up in the liquid medium bathing the cells with the aid of the chemotaxis chamber, multi-cue situations can be produced, in which the synergy or competition between surface and solution gradients can be studied within the defined geometries provided by a micropattern.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been found that the size and geometry of the accessible area can alter and direct the axis of cell polarization and division 2,3,5 , the positions and orientation of pseudopodia 4 , or the locations of junctions between adjacent cells 14 . Cell adhesion and migration depends in large part on the protein composition of a cell's surroundings [15][16][17] , but the relative density of adhesion sites [18][19][20] , as well as density gradients of surface-bound proteins, can influence and bias its spreading and motion 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Favourable biocompatibility: Synthetic polymeric materials are widely used in cartilage tissue engineering scaffolds due to their superior controllability over physicochemical properties. That being said, the surface of synthetic polymers lacks certain receptor-specific binding bioactive molecules of natural materials, such as RGD sequences that are important for cell adhesion and growth migration, and functional differentiation [ 289 ]. Therefore, scaffolds derived from synthetic materials such as PLA, PGA, PLGA are mostly modified with natural polymers or functional groups to create a simulated natural biochemical environment suitable for cell survival.…”
Section: Nanomedicine In Cartilage Repairmentioning
confidence: 99%